(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To evaluate the rate of dislocation in both lateral and posterior approaches Study design: Prospective randomized controlled trial Study setting: Department of Orthopedic Surgery Unit II, Mayo Hospital Lahore, Pakistan Duration: April 2009- December 2011 Material and Methods: Total of 43 patients of hemirathroplasty were included in the study, 22 patients (51.2%) with posterior Moore’s approach and 21(48.8%) with direct lateral approach. Age of the patients was above 55 years. The two groups were otherwise comparable regarding co-morbid factors. All surgeries were performed in the same department. Patients were followed up for three months to analyze the rate of dislocation. In addition we analyzed the dislocation rate for each approach in three groups (Consultant, Senior Registrars and Senior Residents). Results: Overall dislocation rate in the posterior approach was 9% (2/22), whereas in the lateral approach group it was 4.8% (1/21). Dislocation rate was also more in the surgeries performed by junior surgeons. Conclusion: We concluded that because of high mortality associated with dislocations, particularly with posterior approach, the direct lateral approach should be practiced especially by surgical trainees.